Pathways to COVID-19 'community protection'. (July 2020) - Marais, B.J.; Sorrell, T.C.
Abstract: To date, no country has reached a natural COVID-19 epidemic peak and observed peaks essentially reflect the effectiveness of 'lockdown' measures. The major challenge is finding a responsible way out of 'lockdown', given that SARS- CoV-2 is now an established global pathogen. Acknowledging limitations in our knowledge regarding the sufficiency and durability of immune responses following natural SARS Cov-2 infection, we discuss three pathways to 'community protection'. Uncontrolled epidemic spread (route 1; R0  > 2) has been associated with overwhelmed health care systems and high death rates, especially in the vulnerable. Controlled epidemic spread (route 2; effective R0 1–2) can be achieved with limited or strict control of social mixing; strict control will be necessary to ensure that only low-risk individuals become infected, without spill-over to vulnerable groups during their period of infectiousness. It has been demonstrated that local epidemic elimination (route 3; effective R0  < 1) can be achieved through prolonged 'lock down', supplemented by early active case finding with quarantine of close contacts to ensure rapid termination of transmission chains within the community. Although universal availability of a safe and effective vaccine remains the preferred 'exit strategy', this may be hard to achieve and alternative options must be considered with careful consideration of all adverse outcomes – including health, social and economic consequences.